Analysing the Factors of Broadband Adoption in the Households of Libya - Wanis, Hatem Abubaker (2010)
Since deployment and adoption of broadband is still in embryonic stage in Libya, it was thought that this will provide an appropriate context for understanding drivers and barriers of households' adoption of broadband in developing nation perspective. Questionnaire had been used to collect the data for this research. Quantitative method has been used to analyze the data. It has found that there is positive relation between attitudes of households, subjective norm, and perceived behavioral control with broadband adoption in Libya.